(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Submerged fermentation of Pleurotus pulmonarius was carried out for over a period of 7 days in order to obtain phytotoxic metabolites. Separation of the metabolites was carried out using standard methods (mycelia, aqueous, and organic extracts). The antibacterial activity of the metabolites from the three extracts was investigated against Escherichia coli ST2747, Klebsiella pneumonia strain PMK1, Salmonella enterica subsp. enterica sero var typhimurium strain 08-1736, and Pseudomonas aeruginosa VRFPA04 using agar-well diffusion technique. Phytochemical analysis was determined qualitatively and minimum inhibitory and minimum bactericidal concentrations were determined by plate assays. Standard antibiotics were used to compare the antibacterial activity of metabolites using the disk diffusion methods. The antimicrobial assay revealed that only the mycelial extract exhibited activity against the selected test strains. Phytochemical screening showed the presences of three phytoconstituents which include alkaloids, flavonoids, saponins, tan nin, steroids, glycosides, phenols, and anthraquinones at varying concentrations in the mycelia extract. The highest zone of inhibition of the test organism was recorded in K. pneumoniae, while the least was detected in P. aeruginosa. Phytotoxic metabolites obtained through submerged fermentation have been discovered to be antagonistic against pathogenic organisms which could be carried out to develop antimicrobial drugs to combat the menace of drug resistance as witnessed in some synthetic drugs.